Effects of pasture conversion to sugarcane for biofuel production on stream fish assemblages in tropical agroecosystems - Zeni, Jaquelini O. [UNESP]; Hoeinghaus, David J.; Casatti, Lilian [UNESP] (Wiley, 2017)
One of the main causes of biodiversity loss in aquatic ecosystems is instream habitat change associated with land-use change in the drainage basin. Biofuel crop production is an increasingly important driver of land-use change in existing agricultural drainage basins. Conceptually, biofuels such as sugarcane (Saccharum spp.: Poaceea) can provide a sustainable alternative to fossil fuels, but little is known about the consequences of biofuel crop production for biodiversity. Thus, our aim was to investigate if and how the degree of further environmental changes at regional and local scales can influence taxonomic and functional structure of fish assemblages in agroecosystem streams. We quantified drainage basin land use, instream and riparian habitat, and fish assemblages in 38 agroecosystem streams in Brazil with drainage basins experiencing rapid expansion of sugarcane production, and calculated degree of environmental change and corresponding response in taxonomic and functional structure of stream fish assemblages. Procrustes and redundancy analyses tested for correlation between land use and instream habitat and environmental factors correlated with fish assemblage structure, respectively. Previous studies demonstrated relationships between land-use change, instream habitat change and taxonomic and functional structure of stream fish assemblages. Therefore, we used regression to test the hypothesis that degree of environmental change is positively correlated with magnitude of change in taxonomic and functional structure of fish assemblages. Primary gradients of environmental change included conversion of pasture to sugarcane and reduction of stream width, depth and volume. Although drainage basin and instream attributes were not correlated within a year, we detected a legacy effect of land use on instream habitat. The degree of environmental change was not significantly correlated with taxonomic or functional changes in stream fish assemblages in most cases. However, abundances of resistant taxa increased, whereas nektonic functional groups decreased, and the biological response also presented evidence of a legacy effect. Our findings demonstrate that instream habitat and aquatic biodiversity in streams with agricultural drainage basins undergoing rapid conversion to biofuel production likely will not experience the full magnitude of responses in the short term. Therefore, repeated sampling of sufficient duration to account for legacy effects or time lags is needed to test for effects of biofuel expansion on biodiversity, and similarly to assess whether management practices such as riparian zone preservation can benefit biodiversity in agroecosystems.
Keywords: Anthropocene; functional traits; homogenisation; land-use change; legacy effect